2011
DOI: 10.1007/s00216-011-4719-7
|View full text |Cite
|
Sign up to set email alerts
|

Fast capillary electrophoresis–time-of-flight mass spectrometry using capillaries with inner diameters ranging from 75 to 5 μm

Abstract: Fast electrophoretic separations in fused silica capillaries (CE) coupled to time-of-flight mass spectrometry (TOF-MS) are presented. CE separations of the model analytes (epinephrine, norepinephrine, dopamine, histidine, and isoproterenol) under conditions of high electric field strengths of up to 1.25 kV cm(-1) are completed in 20 s. Coupling of CE with TOF-MS is accomplished using a coaxial sheath liquid electrospray ionization interface. The influence of parameters inherent to the interface and their effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
0
30
0
1
Order By: Relevance
“…Chiral analysis of excitatory acids from the brain by CE has been reported (Wang et al, 2011;Wagner et al, 2012). In addition, CE has a potential for high-throughput analysis, and separation times as fast as 20 s have been reported for catecholamines, as well as a fourfold increase in sensitivity by using short separation capillaries with small inner diameters (Grundmann and Matysik, 2011). A sampling approach that further enhances the concentration sensitivity of CE separations is single-drop microextraction; analyte enrichment ranging from B7000-fold for chiral amino acids and up to B30 000-fold for fluorescent dyes has been reported (Alothman et al, 2012).…”
Section: Microseparation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chiral analysis of excitatory acids from the brain by CE has been reported (Wang et al, 2011;Wagner et al, 2012). In addition, CE has a potential for high-throughput analysis, and separation times as fast as 20 s have been reported for catecholamines, as well as a fourfold increase in sensitivity by using short separation capillaries with small inner diameters (Grundmann and Matysik, 2011). A sampling approach that further enhances the concentration sensitivity of CE separations is single-drop microextraction; analyte enrichment ranging from B7000-fold for chiral amino acids and up to B30 000-fold for fluorescent dyes has been reported (Alothman et al, 2012).…”
Section: Microseparation Methodsmentioning
confidence: 99%
“…MS confirmation of analytes detected using LIF is important; however, transferring a particular separation method from a CE-LIF instrument to one with MS detection is challenging because of LIF buffer incompatibilities with MS detection. Recent CE-MS work has shown that separations using smaller inner diameter capillaries (eg, 5 mm) were shown to be less affected by buffer composition (Grundmann and Matysik, 2011).…”
Section: Detection Platforms Compatible With Microanalysismentioning
confidence: 99%
“…where L is the length of the capillary, V is the applied voltage and m is the electrophoretic mobility (3) ; hence, faster separations may be achieved more readily by using short capillaries (4) than by using higher voltages.…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…From Figure 3, detection times for Rh-123 and GSSG-NDA are 9 and 16 min, respectively, leading to a maximum throughput of 3-5 cells h 21 . These flow times can be significantly accelerated, without loss of separation (4) , by reducing the capillary length. For example, a reduction in the capillary length from 1 m to 30 cm, without changing the separation voltage, will result in a ninefold decrease in migration time.…”
Section: Coupling Ce-lif To a Microbeammentioning
confidence: 99%
“…Correspondence to: Mehdi Moini; e-mail: moinim@gwu.edu techniques, such as fast GC and fast LC, as well as supercritical fluid chromatography MS and capillary electrophoresis MS (CE-MS), have been introduced [13][14][15][16][17]. Among these separation techniques, CE is the easiest one to miniaturize since it only requires high voltage power supplies for its operation.…”
mentioning
confidence: 99%